2013
DOI: 10.2166/wst.2013.447
|View full text |Cite
|
Sign up to set email alerts
|

Paraben resistance in bacteria from sewage treatment plant effluents in India

Abstract: Parabens, the antimicrobial preservatives used in cosmetics, food and pharmaceuticals, are often detected in the aquatic environment. Generally, sewage treatment plants (STPs) receive community sewage containing parabens, which are ultimately released into streams/rivers. In this study, bacteria in STP effluents were evaluated for their resistance to parabens. The susceptibility was in the order of Staphylococcus aureus > Bacillus sp. >Escherichia coli > Pseudomonas aeruginosa. Gram-negative bacteria showed le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…For example, the amplified hydrologic pulse of urban ecosystems is expected to change due to the interactive effects of land use and climate change across different areas of the U.S. and elsewhere [79,[93][94][95][96], and this may trigger urban adaptation and evolution of ecosystem structure and function of urban drainage [44,90]. As another example, the number and concentrations of pharmaceutical and personal care products (PPCPs) in the chemical diet of urban watersheds can be expected to increase in the future, and there are questions regarding urban adaptation from individual organisms and ecosystem responses to environmental regulations globally [128][129][130][131]. Additionally, there has been a rise in novel urban hydrologic systems during the Anthropocene era in response to urban adaptations of green roofs, rain gardens, and artificial lakes in cities from humid to arid regions [19,61,132,133].…”
Section: The Future Of Urban Evolutionmentioning
confidence: 99%
“…For example, the amplified hydrologic pulse of urban ecosystems is expected to change due to the interactive effects of land use and climate change across different areas of the U.S. and elsewhere [79,[93][94][95][96], and this may trigger urban adaptation and evolution of ecosystem structure and function of urban drainage [44,90]. As another example, the number and concentrations of pharmaceutical and personal care products (PPCPs) in the chemical diet of urban watersheds can be expected to increase in the future, and there are questions regarding urban adaptation from individual organisms and ecosystem responses to environmental regulations globally [128][129][130][131]. Additionally, there has been a rise in novel urban hydrologic systems during the Anthropocene era in response to urban adaptations of green roofs, rain gardens, and artificial lakes in cities from humid to arid regions [19,61,132,133].…”
Section: The Future Of Urban Evolutionmentioning
confidence: 99%
“…Recent studies confirmed antibacterial resistance of PCPs (parabens, triclosan) from wastewater and surface water [11,71]. Selvaraj et al [11] reported bacterial resistance in common pathogens in effluents of sewage treatment plants in India for parabens and suggested the possible transfer of resistant genes to other pathogenic bacteria in natural waters because of the release of untreated wastewaters directly into the environment. Moreover, the resistant strains have the potency to modify PCPs into toxic compounds [72] which may further affect the organisms.…”
Section: Antibacterial Resistancementioning
confidence: 91%
“…As we are aware, the prevalence of antibiotic-resistant bacteria in hospital, industrial [8], as well as domestic wastewater [9] environment is not uncommon; nevertheless, increasing use of antimicrobial compounds leads to similar problem of resistance in bacteria from sewage and surface water, drinking water, etc. [10][11][12]. Bacterial resistance for PCPs such as parabens in aquatic system is a growing environmental problem [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results suggested that BP had no effect on carbon source metabolism of the bacteria within the periphyton biofilm in all tested concentration levels. Selvaraj et al (2013) evaluated four bacteria strains (Staphylococcus aureus, Bacillus sp., Escherichia coli, Pseudomonas aeruginosa) in sewage treatment plants effluents for their response to parabens, and found that the strains showed resistance up to C5 mg of parabens. The lowest observed effect concentration in an acute toxicity test was 0.7 mg L -1 BP for Vibrio fischeri and 8.5 mg L -1 MP for Photobacterium leiognathi (Bazin et al 2010).…”
Section: Effects On Bacteriamentioning
confidence: 99%